2003
DOI: 10.1249/01.mss.0000089335.85254.89
|View full text |Cite
|
Sign up to set email alerts
|

Demographic Characteristics of Elite Ethiopian Endurance Runners

Abstract: Elite endurance athletes are of a distinct environmental background in terms of geographical distribution, ethnicity, and also having generally traveled farther to school, often by running. These findings may reflect both environmental and genetic influences on athletic success in Ethiopian endurance athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 16 publications
5
97
0
1
Order By: Relevance
“…More of male athletes were between ages 25 -30 years while for the females most of them were between ages 18 -24 years. This was similar to a recent study of the Ethiopian elite runners who were found to have majority between ages of 24-32 years Scott, (2008) [8] . This is probably because after 30 years of age most female retire from sports and settle to other responsibilities including motherhood which reduce their time for active practice.…”
Section: Discussionsupporting
confidence: 91%
“…More of male athletes were between ages 25 -30 years while for the females most of them were between ages 18 -24 years. This was similar to a recent study of the Ethiopian elite runners who were found to have majority between ages of 24-32 years Scott, (2008) [8] . This is probably because after 30 years of age most female retire from sports and settle to other responsibilities including motherhood which reduce their time for active practice.…”
Section: Discussionsupporting
confidence: 91%
“…Alternately, it is possible that the effect of ACTN3 genotype on muscle performance is dependent on other genetic influences, or on environmental variables, that differ between African and non-African populations. For example, many East Africans are subject to environmental influences, such as living and training at altitude and high levels of incidental running during childhood, which play major roles in shaping athletes from this region (12,15) and differ substantially from the childhood experiences of most potential non-African athletes. Such factors may reduce the impact of >-actinin-3 deficiency on the muscle performance of African individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The East African cohort consisted of 198 Ethiopian controls and 76 elite Ethiopian endurance athletes, all members of the Ethiopian junior or senior athletics squad (15). Among the controls, 105 samples were collected from the general Ethiopian population (15), and another 93 samples were collected from the Arsi province, a region known to be the origin of many elite endurance athletes (15). In addition, 158 Kenyan controls and 284 elite endurance runners were included, 67 of whom had represented Kenya in major international distance running competition, and the remainder of whom were competitive in distance running competition at national level within Kenya.…”
Section: Methodsmentioning
confidence: 99%
“…East African runners, in particular Kenyan (Baker & Horton, 2003, Larsen, 2003, Onywera et al, 2006, Ethiopian (Scott et al, 2003) and Eritrean (Lucia et al, 2006) runners have been dominating long-distance running events, especially marathon races, for several years. These findings underline the importance of good knowledge on basic demographic information of runners in analysing their running performances.…”
Section: Introductionmentioning
confidence: 99%